Pendampingan Pembelajaran, Adaptasi Teknologi, dan Penguatan Literasi di Sekolah Dasar Melalui Program Kampus Mengajar - Huraiza Mahmudah (Postgraduate Program, University of Mataram, 2024)
The COVID-19 pandemic has significantly affected the learning process in elementary schools, particularly due to the limitations of face-to-face learning and the low utilization of technology in instructional activities. The Kampus Mengajar program is one of the initiatives under the Merdeka Belajar–Kampus Merdeka policy aimed at assisting schools in improving the quality of learning through strengthening literacy, numeracy, and technology adaptation. This community service activity was conducted at SDN 2 Narmada, West Lombok Regency. The implementation method consisted of several stages, including preparation, observation and analysis of school needs, implementation of learning assistance programs, technology adaptation, and support for school administration. The results indicate that the Kampus Mengajar program had a positive impact on increasing students’ learning motivation, improving literacy and numeracy skills, and enhancing teachers’ understanding in utilizing educational technology. In addition, the program also assisted the school in managing administrative tasks and developing literacy facilities through the establishment of a literacy garden program. Therefore, mentoring activities through the Kampus Mengajar program can provide a tangible contribution to improving the quality of learning in elementary schools, particularly in areas with limited educational facilities and infrastructure.